The meaning of female passivity in traditional Malay literature - Hamdan, Rahimah; Md. Radzi, Shaiful Bahri (Canadian Center of Science and Education, 2014)
In traditional Malay literature, women were often portrayed as individuals who were mentally, physically and spiritually weak. They were incapable of surviving on their own and could only hope to receive help and assistance from the main characters comprising men. In addition, the female characters in the genres of traditional Malay literature were 'silenced' by their authors when faced with certain situations without being given the opportunity to come forward to defend themselves let alone their rights. Their ‘silence’ was also related to their passivity in dealing with life. Thus, this paper will identify the female characters in several selected genres and analyse their level of passivity according to Bardwick’s psychological perspective. The results of this study show that the 'silence' of traditional women marked their ingenuity in handling pressure from the Malay patriarchal society. The 'passivity' of this group was also meant to be a form of indirect aggression over their inability to establish their rights openly in society. This paper shows that the 'silence' of the women in traditional Malay literature does not mean they gave in willingly to every act committed against them, but it was also a ‘subtle’ resistance to the suppression by the patriarchal system as practised in the Malay community.